Constituent phases optimization of modified sulphoaluminate cement and its characteristic of Cl− solidification and resistance to marine erosion. (13th December 2021) - Yuan, Jungang; Li, Shusen; Yan, Jinghua; Wang, Shoude; Lu, Lingchao; Cheng, Xin
Highlights: The replacement ratio of P to S of 9 mol% endowed modified SAC the optimal mechanical property. Excessive Fe2 O3 (less than 50 wt%) and P2 O5 (40–60 wt%) further contributed to the improvement of compressive strength of modified SAC. The solidification ratio of chloride ions of modified SAC increased by 36.0% compared with the reference sample at 90 days. The coefficient of resistance to marine erosion of modified SAC increased by 7.1% compared with the reference sample at 90 days. Abstract: The predominant phase of modified suphoaluminate cement (SAC) was C4 A3 ($, P), which was originated from part replacement of element phosphorus (P) to sulfur (S). For the aim of improving the mechanical property, the ability to solidify chloride ions and the resistance to marine erosion, all constituent phases ratio of modified SAC were optimized by the addition of excessive Fe2 O3 and P2 O5, whose mineralogical composition and properties were analyzed by using XRD, SEM-EDS, TGA and so on. The experimental results indicated that C4 A3 ($, P), 6C2 S∙C3 P, C4 AF as well as unexpected C2 AS were included in clinker system based on the XRD analysis. The replacement ratio of P to S of 9 mol% endowed the modified SAC excellent mechanical property, and excessive Fe2 O3 (less than 50 wt%) as well as P2 O5 (40–60 wt%) were more beneficial to the compressive strength improvement of modified SAC. Moreover, excessive Fe2 O3 and P2 O5 attributed to the improvement of the ability to solidify chloride ions and resistance to marine erosion. The solidification ratio of chloride ions increased by 36.0% while the coefficient of resistance to marine erosion of modified SAC increased by 7.1% at 90 days compared with the control. Furthermore, the addition of P2 O5 may be responsible for the increase of decomposition temperature of hydration products of modified SAC.